Hox and Pbx Factors Control Retinoic Acid Synthesis during Hindbrain Segmentation - Vitobello, Antonio (2011)
In vertebrate embryos, retinoic acid (RA) synthesized in the mesoderm by Raldh2 emanates to the hind-brain neuroepithelium, where it induces anteroposterior (AP)-restricted Hox expression patterns and rhombomere segmentation. However, how appropriate spatiotemporal RA activity is generated in the hindbrain is poorly understood. By analyzing Pbx1/Pbx2 and Hoxa1/Pbx1 null mice, we found that Raldh2 is itself under the transcriptional control of these factors and that the resulting RA-deficient phenotypes can be partially rescued by exogenous RA. Hoxa1-Pbx1/2-Meis2 directly binds a specific regulatory element that is required to maintain normal Raldh2 expression levels in vivo. Mesoderm-specific Xhoxa1 and Xpbx1b knockdowns in Xenopus embryos also result in Xraldh2 downregulation and hindbrain defects similar to mouse mutants, demonstrating conservation of this Hox-Pbx-dependent regulatory pathway. These findings reveal a feed-forward mechanism linking Hox-Pbx-dependent RA synthesis during early axial patterning with the establishment of spatially restricted Hox-Pbx activity in the developing hindbrain.